Fracture and permeability of concrete and rocks - Pijaudier-Cabot, Gilles (Comptes Rendus. Physique, 2021)
Continuum Damage Mechanics provides a framework for the description of the mechanical response of concrete and rocks which encompasses distributed micro-cracking, macro-crack initiation, and then its propagation. In order to achieve a consistent setting, an internal length needs to be introduced to circumvent the difficulties inherent to strain softening and to avoid failure without dissipation of energy. Upon inserting this internal length, structural size effect is captured too. This paper reviews some the progresses achieved by the author since the introduction of the nonlocal damage model in 1987. Among them, the early proposals exhibited a proper description of the inception of failure but a poor one for complete failure since it is not straightforward to model a discrete cracking with a continuum approach. Candidate solutions, e.g. by considering a variable internal length are outlined. Then, the coupled effects between material damage and material permeability are considered. Is is recalled that the permeability of the material should be indexed on the damage growth in the regime of distributed cracking. Upon macro-cracking, there is a change of regime and it is the crack opening that controls the fluid flow in the cracked material. Both regimes may be captured with a continuum damage approach, however.